Tinjauan Yuridis Terhadap Sengketa Penguasaan Tanah Eigendom Verponding (Studi Kasus Putusan NO. 27/PDT.G/2019/PN Soe) - Sajid Munandar Alam; Yossie Maria Yulianty Jakob; Husni Kusuma Dinata (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
The purpose of this study is to determine the legal status of the eigendom verponding land No. 1 AAN after the decision No. 27/Pdt.G/2019/PN Soe, and the legal consequences of the decision No. 27/Pdt.G/2019/PN Soe. The benefit of this research is to contribute to the development of knowledge in general legal studies and specifically in agrarian law, particularly in the context of the control of western lands that have not yet been converted according to the provisions of the Basic Agrarian Law. This research is a type of normative research. The results of this study show: (1) The legal status of the eigendom verponding land No. 1 AAN after the decision No. 27/Pdt.G/2019/PN Soe is valid and has binding legal force because it has been registered and ratified by the Regent of Timor Tengah Selatan, Drs. C Tapatab, on July 27, 1979, as a representative of the Directorate General of Agraria. (2) The legal consequence of decision No. 27/Pdt.G/2019/PN Soe is that nothing can be executed because the judge declared the case inadmissible (Niet Ontvankelijke Verklaard - NO), meaning the substance of the case cannot be examined, but the plaintiff was ordered to pay court fees amounting to IDR 5,811,000 (Five million eight hundred eleven thousand Rupiah). The author's recommendation is that the public should keep and document all land ownership-related documents, that plaintiffs or heirs should file a new lawsuit so that the substance of the case can be continued, that the government should ensure legal certainty in every process of acquiring ownership rights, that the Timor Tengah Selatan Regional Government should issue a final Regional Regulation related to land law, and that judges in the PN Soe Court should dig deeper into the information to resolve the dispute regarding the eigendom verponding land No. 1 AAN.